2021
DOI: 10.1093/reseval/rvab006
|View full text |Cite
|
Sign up to set email alerts
|

Does government support of a few leading universities have a broader impact on the higher education system? Evaluation of the Russian University Excellence Initiative

Abstract: Many governments attempt to improve national higher education through the competitive support of universities. These policy approaches raise questions about the impact on the entire system—both in research and educational—of targeted support for a small number of universities. Addressing challenges in the measurement of university excellence initiatives are among the most vital topics in research evaluation due to the central roles they often play in national research and university policy efforts. Using data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…What remains underexplored is trends in mobility surrounding non-funded universities after the implementation of excellence initiatives. The same study by Lovakov et al (2021) revealed no significant difference in number of recruited young academics between participating and non-participating universities. Taiwan's own WCUP-propelled universities were left to themselves to strategize about acquiring funding, to level up their recruitment of STEM faculty, and to create interdisciplinary research clusters (Fu, 2017), but we have yet to observe trends on the side of the universities that did not receive funding.…”
Section: Excellence Initiatives and Talent Mobilitymentioning
confidence: 78%
See 1 more Smart Citation
“…What remains underexplored is trends in mobility surrounding non-funded universities after the implementation of excellence initiatives. The same study by Lovakov et al (2021) revealed no significant difference in number of recruited young academics between participating and non-participating universities. Taiwan's own WCUP-propelled universities were left to themselves to strategize about acquiring funding, to level up their recruitment of STEM faculty, and to create interdisciplinary research clusters (Fu, 2017), but we have yet to observe trends on the side of the universities that did not receive funding.…”
Section: Excellence Initiatives and Talent Mobilitymentioning
confidence: 78%
“…Meanwhile, the effects on non-funded universities have been mixed. Lovakov et al (2021) find spillover effects of Russia's excellence initiative on the non-benefiting universities. In Germany, Esterhazy (2018) observes that the universities that failed to receive funding during the first two rounds of the excellence initiative had increased pressure to boost their academic reputation, leading to successful funding in the third round.…”
Section: Excellence Initiatives and Talent Mobilitymentioning
confidence: 92%
“…Последствиям получения университетами перечисленных статусов посвящено множество исследований. Проанализированы изменения в вузовской структуре [Меликян, 2014], динамика показателей академической продуктивности в результате проведенных преобразований, в частности рост количества публикаций и межвузовских коллабораций , восприятие происходящих изменений вузовским персоналом и студентами [Романенко, 2018], эффекты реализованных программ для вузов, не получивших специального статуса [Lovakov et al, 2021]. Таким образом, организационные результаты реформирования вузов и произошедшая перестройка межвузовских связей, а также последствия реформ для сотрудников и студентов достаточно хорошо изучены.…”
Section: для цитированияunclassified
“…The consequence, as critics of India’s Institutions of Eminence point out, is that the rest of that nation’s higher education establishments get left behind ( Mittal and Tiwari, 2020 ). Analyses of government-funded university excellence initiatives in other parts of the world such as China ( Zong and Zang, 2019 ), Russia ( Lovakov et al, 2021 ), and Japan ( Yonezawa and Shimmi, 2015 ) all show considerably larger disparities between funded and unfunded institutions at the end of the exercise. These disparities are evident across a range of indicators such as publications in highly cited journals, international collaborations, and the recruitment of talented students and overseas academics.…”
Section: The Growing Inequity Of Growing Inequitymentioning
confidence: 99%